Study of serum amylase levels in Organophosphorus Poisoning patients in a tertiary care hospital in Kolar - K Harshitha, K Harshitha; C R, Vidyasagar; Manjunatha N, Manjunatha N; Prabhavathi K, Prabhavathi K (Journal of Neonatal Surgery, 2025)
Background: One significant prognostic indicator of OP poisoning may be serum amylase. The degree of poisoning was previously determined by measuring the plasma cholinesterase level. Serum amylase is currently advised as a more accurate measure of severity. The purpose of this study is to ascertain whether serum amylase levels are related to the patient's presentation and outcome. Material and Methods: Fifty individuals who were admitted with a history of organophosphorus poisoning participated in a cross-sectional study. Along with other standard tests such as CBC, RFT, LFT, serum pseudocholinesterase, thyroid profile, chest X-ray, USG Abdomen Pelvis, and PFT, the serum amylase level was assessed in 50 individuals who had a history of exposure to organophosphorus substances. Using the Peradeniya Organophosphorus Poisoning (POP) scale and additional variables such as ICU stay/need for a ventilator, discharge/death, and others, the prognosis and clinical outcome of the patients were evaluated. Results: It was statistically significant that the mean POP score for recovered cases was 1.57 and for dying cases it was 5.5. The recovered group's mean serum amylase levels were 50.63, while the deceased group's were 205.4. At the level of serum amylase of 100.55, the sensitivity was 86.667% and Specificity was 100%. Conclusion: The results showed a substantial correlation between serum amylase levels and death in cases of OP poisoning.